Evolutionary Tuning of Transient Receptor Potential Ankyrin 1 Underlies the Variation in Heat Avoidance Behaviors among Frog Species Inhabiting Diverse Thermal Niches. (22nd August 2022) - Saito, Shigeru; Saito, Claire T; Igawa, Takeshi; Takeda, Nodoka; Komaki, Shohei; Ohta, Toshio; Tominaga, Makoto
Abstract: Environmental temperature is a critical factor for all forms of life, and thermal tolerance defines the habitats utilized by a species. Moreover, the evolutionary tuning of thermal perception can also play a key role in habitat selection. Yet, the relative importance of thermal tolerance and perception in environmental adaptation remains poorly understood. Thermal conditions experienced by anuran tadpoles differ among species due to the variation in breeding seasons and water environments selected by parental frogs. In the present study, heat tolerance and avoidance temperatures were compared in tadpoles from five anuran species that spatially and temporally inhabit different thermal niches. These two parameters were positively correlated with each other and were consistent with the thermal conditions of habitats. The species difference in avoidance temperature was 2.6 times larger than that in heat tolerance, suggesting the importance of heat avoidance responses in habitat selection. In addition, the avoidance temperature increased after warm acclimation, especially in the species frequently exposed to heat in their habitats. Characterization of the heat-sensing transient receptor potential ankyrin 1 (TRPA1) ion channel revealed an amphibian-specific alternatively spliced variant containing a single valine insertion relative to the canonical alternative spliced variant of TRPA1, and this novel variant altered the response to thermal stimuli. The two alternatively spliced variants of TRPA1 exhibited different thermal responses in a species-specific manner, which are likely to be associated with a difference in avoidance temperatures among species. Together, our findings suggest that the functional change in TRPA1 plays a crucial role in thermal adaptation processes.